Eficácia do alho como anti-helmíntico em ovinos e bovinos - Santos, Juliano Costa dos (2015)
Garlic have been shown to have anthelmintic activity against common intestinal parasites, but research of the effectiveness of unconventional therapeutic methods is rare. The objective of this research was to evaluate the anthelmintic activity of garlic in ruminants. Four experiments were conducted, two with sheep and two with cattle. In the experiment 1 crossedbred Suffolk sheep with 48 kg body weight were used to the housing conditions allocated in three groups: one was a negative control; as second group was treated with garlic bulb (120g/100kg body weight), administered at regular intervals (1; 7; 14 and 21 day or 1 and 14 day). The same was made on the third group(120g/100kg body weight) but treated with garlic aqueous extract. Repeated the experiment using lambs of the same genetic group with 22 kg body weight. In the experiment 2 ewes and lambs were used to the pasture conditions allocated in two groups, negative control and treated with garlic aqueous extract. Other two experiments were conducted with cattle. In the experiment 1 crossed-breed steers were used to the pasture conditions allocated in three groups: one was the negative control; the second group was treated with garlic bulb (90 or 120g/100kg body weight), administered at regular intervals (days 1; 7; 14 and 21 or 1 and 14); the same was made on the third group but treated with garlic aqueous extract. In the experiment 2, Holstein calves were used to the pasture conditions treated with garlic and garlic aqueous extract (60g/100kg body weight). For all experiments, fecal samples were collected day 0; 7; 14; 21 and 28. The garlic treatments were effective in the reduction of parasite infection in sheep and young cattle.